Analisis Efektivitas Pelaksanaan Pelatihan Berbasis Kompetensi Bagi Calon Tenaga Kerja Lokal di Kabupaten Gresik - Sa'idah, Makrufatus; Muljanto, Muhammad Agus (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
This study aims to analyze the effectiveness of competency-based training programs for local workforce candidates in Gresik Regency, a study at the Gresik Manpower Office and Gresik Vocational House. The effectiveness is seen based on four aspects according to Budiani (2007), namely target accuracy, program socialization, program objectives, and program monitoring. This research uses a qualitative approach with data collection techniques through observation, semi-structured interviews, and documentation involving informants who have an understanding and connection with the training program. Data analysis was conducted using the Miles and Huberman Interactive Model (Miles et al., 2014) through data collection, data condensation, data presentation, and conclusion drawing. The results showed that this competency-based training program has been quite effective for local workforce candidates in Gresik Regency. This can be seen from the analysis of several aspects of effectiveness, namely the target accuracy aspect is considered very appropriate because it has targeted the native Gresik community and job seekers, the program socialization aspect is considered quite effective because it has succeeded in utilizing social media and digital platforms that are easily accessible, the program objectives aspect is considered effective in improving the skills of local workers and reducing unemployment because the training design is based on industry needs, as well as good program monitoring from officers in overseeing the course of training and also post-training through WhatsApp groups, Google Forms, and evaluation meetings. However, strategies and evaluations are still needed to improve this training program in the future so that it is more optimal and has an increasing impact.